Scientific Research Hypotheses Understanding of the Pre-Service Science Teachers at Faculty of Education-Amran University, Yemen - Abddulsalam Sulaiman Dawood Al-Hadabi; Mabrook Saleh Ali Asoudi (Taez University, 2020)
Preparing pre-service science teachers (PSSTs[1]) with the scientific research skills (SRSs) is an ultimate aim of PSSTs' preparation programs. Yet, this study aimed to explore PSSTs' understanding level of SRHs (SRHUL). To this end, an action research (AR) was adopted using a pre-post-test design. In doing so, a multiple choice test consists of 15 items was developed and conducted on a random sample consisted of 120 subjects. Results of the study revealed that participants showed insufficient performance on the test of understanding scientific research hypotheses (SRHUT) for both pre and post-test. Besides, results of t-test showed a significant difference between mean scores of pre-test and post-test which was in favor of post-test. Also results of one-way ANOVA revealed a non-significant difference between or within mean scores of compared groups. Based on the study's results, some recommendations were made. ([1]) For this study, PSSTs can be defined as the 3rd academic year-students who studied fundamentals of educational research course (FERC) at faculty of education-Amran university. In Yemeni universities, PSSTs are prepared to become science secondary school teachers after their graduation (Al-hidabi, 2012). They are exposed to different cultural, professional, and academic courses which FERC is one of the compulsory courses.